2017
DOI: 10.1002/app.45056
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of styrene with acrylated epoxidized soybean oil in an unsaturated polyester resin from propylene glycol and maleic anhydride

Abstract: A nonvolatile, vegetable‐oil based chemical, acrylated epoxidized soybean oil (AESO) was investigated as a replacement of volatile and toxic styrene in one of commercial UPE resins styrene‐(PG‐MA) that is a mixture of styrene and a UPE plastic from propylene glycol and maleic anhydride (PG‐MA). Neither AESO nor PG‐MA was capable of forming a strong matrix, respectively, for glass fiber‐reinforced composites. However, a mixture of AESO and PG‐MA resulted in glass fiber‐reinforced AESO‐(PG‐MA) composites that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 12 publications
(17 reference statements)
1
22
0
Order By: Relevance
“…DCPD-UPE is very different from the PG-IPA-MA or PG-MA we investigated before in terms of its chemical structure and polarity. 18,19 In this study, we found that DCPD-UPE and AESO were miscible and formed a stable homogeneous solution at room temperature. AESO-(DCPD-UPE) could be easily used at room temperature for the preparation of glassfiber-reinforced composites.…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations
“…DCPD-UPE is very different from the PG-IPA-MA or PG-MA we investigated before in terms of its chemical structure and polarity. 18,19 In this study, we found that DCPD-UPE and AESO were miscible and formed a stable homogeneous solution at room temperature. AESO-(DCPD-UPE) could be easily used at room temperature for the preparation of glassfiber-reinforced composites.…”
Section: Introductionmentioning
confidence: 62%
“…The AESO-(DCPD-UPE) resin [ Figure 1(a)] was a stable, homogeneous, clear, easily pourable liquid at room temperature, whereas the AESO-(PG-MA) resin [ Figure 1(b)] was a cloudy, rather viscous mixture at room temperature. AESO-(PG-IPA-MA) 18 and AESO-(PG-MA) 19 had similar appearances and viscous properties; this indicated that DCPD-UPE was more compatible with AESO than PG-IPA-MA or PG-MA.…”
Section: Improved Compatibilitymentioning
confidence: 85%
See 2 more Smart Citations
“…Cationic copolymerization of soybean oil with styrene has been conducted resulting in a rigid thermoset polymer. 26,27 Several studies have also reported synthesis of biobased resin by using commercially available ESO reacted with maleic anhydride. 22 In a few instances, polymerization of CSOs has been reported.…”
Section: Introductionmentioning
confidence: 99%